Water Flow, Solute and Heat Transfer in Groundwater - Yakirevich, Alexander (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Groundwater is an essential and vital water resource for drinking water production, agricultural irrigation, and industrial processes. Having a better understanding of physical and chemical processes in aquifers enables more reliable decisions and reduces investments concerning water management. This Special Issue on "Water Flow, Solute, and Heat Transfer, in Groundwater" of Water focuses on the recent advances in groundwater dynamics, and it includes high-quality papers that cover a wide range of issues on different aspects related to groundwater: protection from contamination, recharge, heat transfer, hydraulic parameters estimation, well hydraulics, microbial community, colloid transport, and mathematical models. This integrative volume aims to transfer knowledge to hydrologists, hydraulic engineers, and water resources planners, who are engaged in the sustainable development of groundwater resources.